Hubungan Pendidikan Agama Islam dalam Lingkungan Keluarga Terhadap Akhlak Remaja Di Desa Podoluhur - Mungawanah, Fiatul; Subarkah, Imam (IAINU Kebumen, 2025)
This study aims to determine the extent of the relationship between Islamic religious education provided by parents in the family environment to adolescent morals. This study uses a quantitative approach with a correlation research type. The analysis techniques used in this study are research instrument testing (validity testing and reliability testing), descriptive statistical analysis, assumption testing, and product moment correlation analysis. The results of this study indicate a strong relationship between Islamic religious education in the family environment and adolescent morals which has an r table of 0.563 which is obtained from the results of product moment calculations using the SPSS application.